Java EE 8 application development : develop enterprise applications using the latest versions of CDI, JAX-RS, JSON-B, JPA, Security, and more - Heffelfinger, David R. (Packt Publishing, 2017)
Java EE is an Enterprise Java standard. Applications written to comply with the Java EE specification do not tie developers to a specific vendor; instead they can be deployed to any Java EE compliant application server. The book will cover the latest changes to the Java EE specification and turn non-enterprise Java developers into enterprise ...